SAL0114: a novel deuterated dextromethorphan-bupropion combination with improved antidepressant efficacy and safety profile - Xiao, Ying; Hu, Xuefeng; Xing, Wei; Yan, Jie; Wang, Ruhuan; Li, Xiaoqing; Li, Jiahuan; Zhang, Zhixin; Sun, Jingchao; Wu, Junjun (Frontiers in Pharmacology, 2024)
Background: Esketamine, the first Food and Drug Administration-approved fast-acting antidepressant, has limited use because of its addictive properties. Although the combination of dextromethorphan and bupropion partially addresses the limitations of esketamine, concerns remain regarding neurologic side effects related to dextromethorphan metabolites, and seizure risks associated with high-dose bupropion. SAL0114, a novel formulation combining deuterated dextromethorphan (in which hydrogen atoms are replaced with deuterium) with bupropion, seeks to enhance dextromethorphan stability through deuteration of its metabolic sites. This approach is expected to increase antidepressant efficacy, reduce metabolite-induced safety issues, and allow for lower bupropion dosages.Methods: Radioligand competition binding assays were used to evaluate the impact of deuterium substitution on the in vitro activity of dextromethorphan and its metabolite, dextrorphan. In vitro hepatic microsomal stability and in vivo mouse pharmacokinetic assays were performed to assess the effects of deuteration on dextromethorphan stability. Two mouse models of behavioral despair were used to determine the antidepressant and synergistic effects of deuterated dextromethorphan and bupropion. Additionally, a reserpine-induced hypothermia rat model and an ammonia-induced cough mouse model were used to assess the in vivo effects from a pathological perspective.Results: Deuterated dextromethorphan maintained the same in vitro activity as dextromethorphan while exhibiting twice the metabolic stability both in vitro and in vivo. Combination with bupropion further improved its in vivo stability, increasing the exposure by 2.4 times. The combination demonstrated efficacy and synergistic effects in all tested animal models, showing superior efficacy compared with the dextromethorphan-bupropion combination.Conclusions: Deuteration improved dextromethorphan metabolic stability without altering its in vitro activity. Bupropion enhanced this stability and synergistically boosted the antidepressant effect by increasing deuterated dextromethorphan exposure in vivo. This enhanced metabolic stability suggests a reduction in dextromethorphan metabolites associated with clinical neurological side effects. Consequently, SAL0114 is hypothesized to offer improved efficacy and safety compared with the non-deuterated combination, potentially allowing for lower bupropion dosages. Further clinical studies are required to confirm these preclinical findings.